对国有企业产权结构和行为的研究 = Analyzing the structure and behavior of China's state-owned enterprises - 田文顺 Tian, Wenshun|谭秀芹 Tan, Xiuqin (2008)
China's small-sized enterprises (those with total assets of less than 10 million Chinese yuan) have started their reforms since 1980s through leasing, contracting, sales, management on trust and share-holding. However, such reforms are not very effective due to the internal structure of these enterprises. Leasing may lead to cheating by the leaseholder while the contractors are only responsible for profits but not for losses because of short-sighted behavior. The idea selling such enterprises may be good but few Chinese individuals can afford it due to lack of capital. On the other hand, such a practice may also result in the loss of state assets or bribery.